Tuneable Time Delay in the Burst Release from Oxidation‐Sensitive Polymersomes Made by PISA. Issue 46 (11th October 2021) - Sobotta, Fabian H.; Kuchenbrod, Maren T.; Gruschwitz, Franka V.; Festag, Grit; Bellstedt, Peter; Hoeppener, Stephanie; Brendel, Johannes C.
Abstract: Reactive polymersomes represent a versatile artificial cargo carrier system that can facilitate an immediate release in response to a specific stimulus. The herein presented oxidation‐sensitive polymersomes feature a time‐delayed release mechanism in an oxidative environment, which can be precisely adjusted by either tuning the membrane thickness or partial pre‐oxidation. These polymeric vesicles are conveniently prepared by PISA allowing the straightforward and effective in situ encapsulation of cargo molecules, as shown for dyes and enzymes. Kinetic studies revealed a critical degree of oxidation causing the destabilization of the membrane, while no release of the cargo is observed beforehand. The encapsulation of glucose oxidase directly transforms these polymersomes into glucose‐sensitive vesicles, as small molecules including sugars can passively penetrate their membrane. Considering the ease of preparation, these polymersomes represent a versatile platform for the confinement and burst release of cargo molecules after a precisely adjustable time span in the presence of specific triggers, such as H2 O2 or glucose. Abstract : Polymersomes made by PISA based on thioether‐functionalized polymers as membrane‐forming block show a spontaneous membrane destabilization once a critical degree of oxidation is reached. Fine‐tuning of the degradation time can be performed either by adjusting the membrane thickness or by partial pre‐oxidation and can be further exploited to tailor the burst release of encapsulated dyes or enzymes in the presence of specific triggers.